Analysis of Online Social Network Connections for Identification of Influential Users - Al-Garadi, Mohammed Ali; Varathan, Kasturi Dewi; Ravana, Sri Devi; Ahmed, Ejaz; Mujtaba, Ghulam; Khan, Muhammad Usman Shahid; Khan, Samee U. (Association for Computing Machinery, 2018)
Online social networks (OSNs) are structures that help users to interact, exchange, and propagate new ideas. The identification of the influential users in OSNs is a significant process for accelerating the propagation of information that includes marketing applications or hindering the dissemination of unwanted contents, such as viruses, negative online behaviors, and rumors. This article presents a detailed survey of influential users’ identification algorithms and their performance evaluation approaches in OSNs. The survey covers recent techniques, applications, and open research issues on analysis of OSN connections for identification of influential users.